Risk factors for postoperative delirium following total hip or knee arthroplasty: A meta-analysis - Zhao, Jinlong; Liang, Guihong; Hong, Kunhao; Pan, Jianke; Luo, Minghui; Liu, Jun; Huang, Bin (Frontiers in Psychology, 2022)
Objectives: The purpose of this study was to identify risk factors for delirium after total joint arthroplasty (TJA) and provide theoretical guidance for reducing the incidence of delirium after TJA. Methods: The protocol for this meta-analysis is registered with PROSPERO (CRD42020170031). We searched PubMed, the Cochrane Library and Embase for observational studies on risk factors for delirium after TJA. Review Manager 5.3 was used to calculate the relative risk (RR) or standard mean difference (SMD) of potential risk factors related to TJA. STATA 14.0 was used for quantitative publication bias evaluation. Results: In total, 25 studies including 3,767,761 patients from 9 countries were included. Old age has been widely recognized as a risk factor for delirium. Our results showed that the main risk factors for delirium after TJA were patient factors (alcohol abuse: RR = 1.63; length of education: SMD = -0.93; and MMSE score: SMD= -0.39), comorbidities (hypertension: RR = 1.26; diabetes mellitus: RR = 1.67; myocardial infarction: RR = 17.75; congestive heart failure: RR = 2.54; dementia: RR=17.75; renal disease: RR= 2.98; history of stroke: RR= 4.83; and history of mental illness: RR=2.36), surgical factors (transfusion: RR = 1.53; general anesthesia: RR = 1.10; preoperative albumin: SMD = -0.38; preoperative hemoglobin: SMD = -0.29; postoperative hemoglobin: SMD = -0.24; total blood loss: SMD = 0.15; duration of surgery: SMD = 0.29; and duration of hospitalization: SMD = 2.00) and drug factors (benzodiazepine use: RR = 2.14; ACEI use: RR= 1.52; and beta-blocker use: RR= 1.62). Conclusions: Multiple risk factors were associated with delirium after TJA. These results may help doctors predict the occurrence of delirium after surgery and determine the correct treatment. Registration PROSPERO ID CRD42020170031